Theoretical Foundations of the Functioning of the Russian Securities Market and the Problem of Categorizing Investors. ("Journal "U". Economy. Management. Finance.", 2021)
This article examines the fundamentals of the functioning of the Russian securities market and the problem of categorizing investors, which at the moment does not allow unqualified investors to be fenced off from rash risks in the securities market, associated with the ease of obtaining the status of a qualified investor
Keywords: financial market; investor; securities market; risk; instrument